Standard Assessment Model for Scientific Integration-Interconnection as Material for Evaluation of Vision and Mission Achievement - Dewanti, Sintha Sih (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to develop a standardized assessment model of scientific integration-interconnection, which begins with conducting a literature review and needs assessment, setting goals, developing initial products, validating contents, testing readability, testing instruments, analyzing results, and ending with an interpretation of the results of the assessment. The method used is Research and Development. Testing of the assessment instruments was carried out for each element of the Tridharma of Higher Education, namely 76 lesson plans, 139 research and development works, and 41 community service works. The scientific integration-interconnection assessment model has characteristics according to the structure of the second order model, with the first order being 4 scientific integration-interconnection domains (philosophical domain, material domain, methodological domain, and strategic domain) and the second order is 15 aspects of scientific integration-interconnection. Data analysis techniques using Aiken-V, Exploratory Factor Analysis/EFA and Confirmatory Factor Analysis/CFA, Omega, Item Response Theory approach of polytomous scoring, and descriptive statistics. The assessment model is feasible, fulfilling the criteria of content validity, construct validity (p-value = 0.11949 and RMSEA = 0.027), estimated instrument reliability (Î± = 0.816), and construct reliability (É·Â =0.939). The scoring used the GRM approach with good quality in terms of the results of the 94% item fit test with an item discrimination index of 0.655 < DISCi < 1.153 and the average item difficulty level of -1.965 < DIFFi < -0.662.